The Evolving Concept of the Blood Brain Barrier (BBB): From a Single Static Barrier to a Heterogeneous and Dynamic Relay Center - Villabona-Rueda, Andres; Erice, Clara; Pardo, Carlos A.; Stins, Monique F. (Frontiers in Cellular Neuroscience, 2019)
The blood-brain-barrier (BBB) helps maintain a tightly regulated microenvironment for optimal central nervous system (CNS) homeostasis and facilitates communications with the peripheral circulation. The brain endothelial cells, lining the brain’s vasculature, maintain close interactions with surrounding brain cells, e.g. astrocytes, pericytes and perivascular macrophages. This function facilitates critical intercellular crosstalk, giving rise to the concept of the neurovascular unit (NVU). The steady and appropriate communication between all components of the NVU is essential for normal CNS homeostasis and function, and dysregulation of one of its constituents can result in disease. Among the different brain regions, and along the vascular tree, the cellular composition of the NVU varies. Therefore, differential cues from the immediate vascular environment can affect BBB phenotype. To support the fluctuating metabolic and functional needs of the underlying neuropil, a specialized vascular heterogeneity is required. This is achieved by variances in barrier function, expression of transporters, receptors, and adhesion molecules. This mini-review will take you on a journey through evolving concepts surrounding the BBB, the NVU and beyond. Exploring classical experiments leading to new approaches will allow us to understand that the BBB is not merely a static separation between the brain and periphery but a closely regulated and interactive entity. We will discuss shifting paradigms, and ultimately aim to address the importance of BBB endothelial heterogeneity with regard to the function of the BBB within the NVU, and touch on its implications for different neuro-pathologies.